ARSITEKTUR TEKNOLOGI WEBSERVER BERBASIS MINI PC DENGAN RASPBERRY PI - Erick Fernando (JURNAL AKADEMIKA)
Development of a website in world of the Internet requires a webserver. The Development Webserver is something which is extremely important in providing services to clients that will access a website. Construction of this webserver using a mini pc technology architecture with Raspberry Pi device. Raspberry Pi is a Mini PC-based open source operating system as an application that uses Xampp webserver. This application is an application that is very powerful and widely used by users. Webserver architecture that uses a mini pc expected one of the alternativesin development webserver. With so can mengeffisienkan and mendinamiskan use hardware devices